2019
DOI: 10.3390/catal9020128
|View full text |Cite
|
Sign up to set email alerts
|

Enter the Tubes: Carbon Nanotube Endohedral Catalysis

Abstract: The unique morphological characteristics of carbon nanotubes (CNTs) present the intriguing opportunity of exploiting the inner cavity for carrying out chemical reactions. Such reactions are catalysed either by the individual tubes that function both as catalysts and nanoreactors or by additional catalytic species that are confined within the channel. Such confinement creates what is called “confinement effect”, which can result in different catalytic features affecting activity, stability and selectivity. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 70 publications
2
15
0
Order By: Relevance
“…Furthermore, the following oxidation step may have partially opened the ends of the nanotubes, which can be a possible explanation of the peak observed at lower reduction temperatures. This agrees well with results published by Iglesias et al [74] …”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Furthermore, the following oxidation step may have partially opened the ends of the nanotubes, which can be a possible explanation of the peak observed at lower reduction temperatures. This agrees well with results published by Iglesias et al [74] …”
Section: Resultssupporting
confidence: 94%
“…[65,73] Furthermore, the following oxidation step may have partially opened the ends of the nanotubes, which can be a possible explanation of the peak observed at lower reduction temperatures. This agrees well with results published by Iglesias et al [74] . Moreover, it can be observed that an increased Ni content produces a shift of the reduction peak of NiO located at 290°C to lower reduction temperature.…”
Section: Characterization Of the Catalystssupporting
confidence: 94%
“…The covalent and noncovalent functionalizations are called exohedric functionalizations. The endohedric functionalization of CNTs happens when atoms and small molecules are found inside the CNTs [187,188].…”
Section: Carbon Nanotubes-modified Electrodesmentioning
confidence: 99%
“…Tubular structures with tunable monodisperse diameters in the nanometer scale are attracting a lot of attention in nanosciences lately. In recent years, nanotubes have been recognized as an ideal 1D nano-platform appealing for applications to be potential catalytic nanoreactors for energy conversion application [60][61][62]. In parallel, synthesis of 2D and 3D nanostructures with permanent polarization has shown interesting activities due to their capacities of generation and separation of charge carriers (e − /h + ) [63], resulting in a new type of photoactive material [64].…”
Section: Imogolite Clay Nanotubes (Int)mentioning
confidence: 99%